Gut Bacterial Composition and Functional Potential of Tibetan Pigs Under Semi-Grazing - Niu, Hui; Feng, Xi-Ze; Shi, Chun-Wei; Zhang, Di; Chen, Hong-Liang; Huang, Hai-Bin; Jiang, Yan-Long; Wang, Jian-Zhong; Cao, Xin; Wang, Nan; Zeng, Yan; Yang, Gui-Lian; et al. (Frontiers in Microbiology, 2022)
Gut bacterial community plays a key role in maintaining host health. Tibetan pig (Sus scrofa), an ancient breed in China, has been known for its high adaptability to harsh environments and meat quality. To understand the underlying mechanisms facilitating to shape these unique features, in this study, 16S rRNA sequencing using pig feces and subsequent bacterial functional prediction were performed. Also, the gut bacteria of two other breeds of pigs, Barkshire and Landrace, were examined for comparison. It was revealed that the structure of bacterial community in Tibetan pigs appeared to be more complex, and the relative abundances of dominant bacterial families varied inversely with those of the other pigs, the proportion of Firmicutes in Tibetan pigs was lower, however, Bacteroides, Fibrobacterota, Lachnospiraceae, Oscillospiraceae, and Ruminococcaceae were higher. Bacterial functional prediction revealed that the dominant flora in Tibetan pig was more correlated with functions regulating the hosts’ immune and inflammatory responses, such as NOD-like_receptor_signaling_pathway, and vitamin metabolism. In addition, in Tibetan pig, the taxonomic relationships in the gut bacteria on day 350 was closer than those on earlier stages. Furthermore, gender played a role on the composition and function of bacterial inhabitants in gut, of which for boars was more correlated to drug resistance and xenobiotics metabolism of the host compared to the sows’. In sum, our preliminary study on the gut bacterial composition of Tibenan pig provided an insight in the underlying host-microorganism interactions, emphasizing the role of intestinal bacteria in the context of modulating host’s immune system and host development.